PENGARUH PELATIHAN KERJA DAN KOMPETENSI KARYAWAN TERHADAP KINERJA KARYAWAN FUNGSI PRODUCTION AND PROJECT PADA PT PERTAMINA HULU KALIMANTAN TIMUR - Shalma Amarta FPNA; Widayanto Widayanto; Sudharto Prawata Hadi (Universitas Diponegoro, 2025)
Workers with good performance can complete their tasks according to the targets that have been set and can realize the success of achieving the company's goals. The Production and Project function has workers with low performance because it is suspected of having a decrease in workers who take training and workers who do not have the competence according to their positions. This type of research is quantitative research with the type of research, namely explanatory research. This study used a population of 100 permanent workers in the Production and Project function of PT Pertamina Hulu East Kalimantan. The analysis tests in this study include validity tests, reliability tests, classical assumptions, correlation coefficients, determination coefficients, linear regressions and significance tests with the help of SPSS IBM 25 software. The conclusion of this study is that the job training variable has a positive and significant effect on employee performance, the employee competency variable has a positive and significant effect on employee performance, and the job training and employee competency variables have a positive and significant effect on employee performance.